2016
DOI: 10.1007/s10714-015-2013-2
|View full text |Cite
|
Sign up to set email alerts
|

Shear-free dust solution in general covariant Hořava–Lifshitz gravity

Abstract: In this paper, we have studied non stationary dust spherically symmetric spacetime, in general covariant theory (U (1) extension) of the Hořava-Lifshitz gravity with the minimally coupling and non-minimum coupling with matter, in the post-newtonian approximation (PPN) in the infrared limit. The Newtonian prepotential ϕ was assumed null. The aim of this work is to know if we can have the same spacetime, as we know in the General Relativity Theory (GRT), in Hořava-Lifshitz Theory (HLT) in this limit. We have sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The junction conditions across the surface of a collapsing star were derived under the (minimal) assumption that the junctions must be mathematically meaningful in terms of distribution theory. Lately, gravitational collapse in this setup was investigated and various solutions were constructed [141][142][143].…”
Section: B With Projectability and U(1) Symmetrymentioning
confidence: 99%
“…The junction conditions across the surface of a collapsing star were derived under the (minimal) assumption that the junctions must be mathematically meaningful in terms of distribution theory. Lately, gravitational collapse in this setup was investigated and various solutions were constructed [141][142][143].…”
Section: B With Projectability and U(1) Symmetrymentioning
confidence: 99%
“…Recent literature on gravitational collapse in HL theory has shown that very little effort has been made to understand the theory even classically [14]. Some of the previous works published by three of the authors have attempted to fill the gap [15] [16] [17]. The present paper is a continuation of our previous papers to understand the HL theory in the IR.…”
Section: Introductionmentioning
confidence: 79%
“…It should be noted that the techniques used here to find a solution, that is, separation of variables, was used before in our previous paper [17], working with timelike dust fluid. There, we found interesting results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation